Physical and insecticidal durability of PermaNet® 3.0 and Olyset® plus piperonyl butoxide-synergist insecticide-treated nets in Sierra Leone: results of durability monitoring from 2020 to 2023 - Raymond Kiprop Sudoi; Keith Esch; Frederick Yamba; Laurent Iyikirenga; Charlene Youssef; Prince Nallo; Isabel Swamidoss; Carla Mapp; Dennis Marke; Samuel Juana Smith; Ronald Carshon-Marsh; Musa Sillah-Kanu; et al. (Malaria Journal)
Abstract Background The performance of two piperonyl butoxide (PBO-synergist) insecticide-treated net (ITN) brands, PermaNet® 3.0 and Olyset® Plus, were evaluated under field conditions in two neighboring districts in Sierra Leone over 36 months to estimate median ITN survival, understand insecticidal efficacy, and identify factors influencing ITN durability. This assessment can help guide future PBO-synergist ITN procurement and replacement strategies. Methods This prospective study tracked 370 households and 652 campaign-distributed ITNs from 2020, followed annually for 36 months. Districts were purposefully selected based on shared characteristics. Household surveys were conducted, and 30 ITNs per round were tested for bioefficacy and chemical residue. Key indicators included ITN survival, 24-h mosquito mortality, and chemical content reduction compared to manufacturer targets doses. Cox proportional hazard models identified factors influencing ITN survival. Results Median useful life was 3.0 (95% CI 2.7–3.5) years for PermaNet® 3.0 ITNs in Bo and 2.2 (95% CI 2.0–2.4) years for Olyset® Plus ITNs in Moyamba. PermaNet® 3.0 ITNs displayed 13% 24-h mortality against pyrethroid-resistant mosquitoes on roof panels, with a 46% reduction in PBO content 34 months post-distribution. Olyset® Plus ITNs had 3% f24-hour mortality against pyrethroid-resistant mosquitoes, with a 77% reduction in PBO content. Several factors were associated with improved ITN survival, including cohort ITNs from Bo (adjusted hazard ratio [aHR] = 0.33, p < 0.001), households without children under five (CU5) (aHR = 0.64, p = 0.003), highest socio-economic status tertile (aHR = 0.63, p = 0.016), exposure to social and behaviour change (SBC) messages combined with positive net attitudes (aHR = 0.63, p = 0.008), lack of food storage in sleeping spaces (aHR = 0.56, p = 0.006), exclusive adult use of ITNs (aHR = 0.72, p = 0.048), net folding when not in use (aHR = 0.67, p = 0.015), and drying nets outside (aHR = 0.44, p = 0.008). Conclusion ITNs in Bo outperformed those in Moyamba in both physical and insecticidal performance. However, ITN survival is highly context specific, and further investigation into field performance of new ITN types is necessary across diverse epidemiological settings.